The Effects of Sedentariness on Psychological (Self- Esteem) and Physical (Body Fat Mass) Aspects in Male and Female Students of University of Tehran - Jamal Fazel; Amir Abbasgholipour; Nima Gharedaghi (University of Tehran, 2011)
The role of higher education is to educate all individuals and it includes not only the intelligence but also the psychological and physiological aspects. The aim of this study was to investigate the effect of sedentariness on self-esteem and body fat mass in students of University of Tehran. The statistical population of the study consisted of all students of University of Tehran and 320 subjects were randomly selected as the sample. Independent t test and Pearson correlation coefficient were used to analyze the data. The results showed that 62% of subjects were sedentary and 38% had sufficient activity. Average body fat percent in all subjects was 26.14% (S.D±6.53). 79% of all students had high self-esteem and 21% had low self-esteem. There was a significant difference between male and female subjects in physical activity. Also, there was no significant difference in body fat mass between active and sedentary subjects. Results did not show any significant relationship between physical activity level and low and high self-esteem.